2022
DOI: 10.3390/cells11030549
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics: An Emerging Approach to Understand Pathogenesis and to Assess Diagnosis and Response to Treatment in Spondyloarthritis

Abstract: Spondyloarthritis (SpA) is a group of rheumatic diseases whose pathogenesis relies on a complex interplay between genetic and environmental factors. Over the last several years, the importance of the alteration of the gut microbiota, known as dysbiosis, and the interaction of bacterial products with host immunity have been highlighted as intriguing key players in SpA development. The recent advent of the so called “-omics” sciences, that include metabolomics, opened the way to a new approach to SpA through a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
(69 reference statements)
0
3
0
3
Order By: Relevance
“…Studies on metabolomics have gained attention in recent years. This has relevance to understanding pathogenesis, diagnosis and response to treatment in AS [60].…”
Section: Metabolomicsmentioning
confidence: 99%
“…Studies on metabolomics have gained attention in recent years. This has relevance to understanding pathogenesis, diagnosis and response to treatment in AS [60].…”
Section: Metabolomicsmentioning
confidence: 99%
“…Algumas proteínas podem estar envolvidas como claudina 1, claudina 4, zônula occludens, ocludina e VE-caderina, o que resulta no comprometimento das funções de barreira epitelial e endotelial do intestino, levando ao aumento dos níveis séricos de produtos bacterianos, que estão relacionados à inflamação na Espondilite Anquilosante (EA). As interações destas com células imunes, como a célula linfoide inata tipo 3 (ILC3), contribuem para a produção de IL-23, uma citocina fundamental na patogênese dessa doença (RIZZO et al, 2022).…”
Section: Revisão Sistemáticaunclassified
“…Estudo metabolômico, que consiste na identificação de pequenas moléculas (metabólitos) no sistema imunológico, identificou que a diminuição de colina (vitamina B8) promove deposição ectópica de gordura em pacientes com EA, bem como a diminuição da 25-hidroxivitamina D3-peroxilactona, um metabólito de 25(OH)D3 produzido no rim. Outro estudo averiguou que ácidos graxos de cadeia curta (AGCCs) desempenham diversos papéis funcionais na formação do sistema imunológico, regulando as funções de várias células imunes, como macrófagos, células dendríticas, células NKT, células T helper 1 (Th1) e células T reguladoras (Tregs), inibindo a histona desacetilase (HORTA-BAAS; SANDOVAL-CABRERA; ROMERO-FIGUEROA, 2021;RIZZO et al, 2022).…”
Section: Revisão Sistemáticaunclassified
See 1 more Smart Citation
“…Previous studies have demonstrated distinct fecal (12) and serum metabolomic signatures in PsA compared with both rheumatoid arthritis (RA) and healthy individuals (13,14), which correlated to specific cytokines and clinical features. Hence, assessment of intestinal permeability and metabolic profiling of biofluids has an emergent role in exploring the contribution of host-microbiota interactions to the pathogenesis and treatment response of immune-mediated arthritis (15). The lactuloseto-mannitol ratio (LMR) assay is an established test for evaluating gut barrier integrity, whereas 1 H nuclear magnetic resonance (NMR) is a high-throughput, reproducible tool for "global metabolomic profiling," assessing a broad range of host and microbial metabolites across a range of biofluids.…”
Section: Introductionmentioning
confidence: 99%